CEO Powerful Features on Conditional and Unconditional Conservatism - et. al., Saeedeh Rezaee, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The present study aimed to investigate the characteristics of CEO capabilities on the conditional and unconditional conservatism in companies listed on Tehran Stock Exchange. In order to test research hypotheses after collecting and screening the initial data a sample consisting of companies listed on Tehran Stock Exchange, up to 142 companies in a period of 6 years (2012-2017) was studied. Excel was used to calculate and classify the research variables. Then, using the multiple regression analysis in Eviews, we test the research hypotheses. The results of the research showed that the CEO abilities do not have a positive and significant effect on conditional conservatism but have a positive and significant on conditional conservatism.